2008
DOI: 10.1248/bpb.31.469
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Treatment of L-Isoleucine Ameliorates Glucose Metabolism in Glucose-Intolerant and Diabetic Mice

Abstract: It is well known that amino acids, one of the three major classes of nutrients, are involved in the metabolism of carbohydrates.1,2) Among various amino acids, L-leucine (leucine) and L-isoleucine (isoleucine) show potent activity for controlling blood glucose. In normal or cirrhotic rats, acute administration of leucine or isoleucine improves the glucose tolerance curve after an oral glucose challenge, 3,4) while chronic leucine supplementation reduces obesity and improves glucose metabolism in mice on a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 12 publications
1
39
0
1
Order By: Relevance
“…In BCATm 2/2 mice, fasting blood glucose and fasting serum insulin levels were decreased by 33% and 67%, respectively, and the Homeostasis Model Assessment for Insulin Resistance index was significantly lower than that of wild-type mice [25]. Similarly, increasing leucine intake and the administration of isolecine have been reported to improve insulin sensitivity in mice fed a high-fat diet, although the multiple mechanisms had not been illustrated well [26,27]. It has been known that dietary supplementation with BCAAs exhibits potential benefit to the metabolic profile.…”
Section: Discussionmentioning
confidence: 99%
“…In BCATm 2/2 mice, fasting blood glucose and fasting serum insulin levels were decreased by 33% and 67%, respectively, and the Homeostasis Model Assessment for Insulin Resistance index was significantly lower than that of wild-type mice [25]. Similarly, increasing leucine intake and the administration of isolecine have been reported to improve insulin sensitivity in mice fed a high-fat diet, although the multiple mechanisms had not been illustrated well [26,27]. It has been known that dietary supplementation with BCAAs exhibits potential benefit to the metabolic profile.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that isoleucine supplement could prevent the tissue triglycerides accumulation (Nishimura et al 2010) and balance blood glucose (Ikehara et al 2008). For example, gavage administration of isoleucine has been shown to decrease the accumulation of tissue triglyceride via increasing expression of PPARa and UCPs (Nishimura et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In those mice, fasting blood glucose and insulin concentrations were decreased and HOMA-IR was significantly lower than in wild-type mice [19] . Furthermore, administration of leucine or isoleucine improved insulin sensitivity in mice with high-fat diets [20,21] . BCAAs were also shown to temporarily increase plasma insulin concentrations in healthy young men, although plasma glucose concentrations were not altered [22] .…”
Section: Insulin Resistancementioning
confidence: 99%